A new one-step deposition approach of graphene nanoflakes coating using a radio frequency plasma: Synthesis, characterization and tribological behaviour. (March 2022) - Aissou, Taki; Braidy, Nadi; Veilleux, Jocelyn
Abstract: Graphene is an emerging solid lubricant that improves the tribological properties of materials by lowering the coefficient of friction and reducing wear. However, the industrial-scale fabrication of graphene is still limited by the lack of a fast, inexpensive, and efficient coating deposition method on large areas. Here, we developed a new one-step process in which graphene nanoflakes (GNFs) are synthesized in-flight by methane decomposition using an inductively-coupled plasma (ICP) torch and are uniformly sprayed over stainless-steel substrates with a deposition rate of 25 µm/min. The uniform nanostructure and quality of the GNFs are demonstrated by transmission electron microscopy, scanning electron microscopy and Raman spectroscopy. Using a ball-on-three-plates tribometer, the friction coefficient of the GNFs-coated steel decreases significantly from 0.90 to 0.17 (10 N load) and the corresponding wear rate decreases by a factor of ~10 compared to the uncoated steel. The wear results are discussed in the framework of a frictional behaviour mechanism and we argue that the wear improvement by the GNFs coating is explained by self-lubrication. Graphical Abstract: ga1 Highlights: Uniform graphene nanoflakes (GNFs) coatings were syhnthesized and sprayed by thermal plasma on stainless-steel substrates. The prepared GNFs-coating showed high quality and high purity. The GNFs solid lubricant coating effectively reduced the coefficient of friction and significantly improved wear resistance.